Claudin h Is Essential for Hair Cell Morphogenesis and Auditory Function in Zebrafish - Gong, Jie; Qian, Peipei; Hu, Yuebo; Guo, Chao; Wei, Guanyun; Wang, Cheng; Cai, Chengyun; Wang, Haibo; Liu, Dong (Frontiers in Cell and Developmental Biology, 2021)
Hereditary hearing loss caused by the defects of hair cells is one of the most common birth diseases, whose nosogenesis is also unclear due to that a majority of genes required for audition remain unidentified. Claudins are one kind of transmembrane proteins that constitute the most important components of the tight junctions and play important roles in the formation of the paracellular barrier as well as neurodevelopment. In this study, we investigated the function of claudin h in the hair cell morphogenesis and auditory function on the zebrafish model. The results of in situ hybridization showed that claudin h was specifically localized in the otic vesicle and neuromasts in zebrafish embryos. The deficiency of claudin h caused significant reduction of otic vesicle size and loss of utricle otolith. Moreover, the startle response and vestibulo-ocular reflex experiments discovered that loss of claudin h led to dramatic hearing loss and vestibular dysfunction, respectively. Importantly, the confocal results showed that compared to the control zebrafish, the number of three different cristae hair cells was significantly reduced in claudin h morphants and mutants together with the shortened kinocilia. Similarly, the deficiency of claudin h also caused the loss of hair cells in neuromast and these phenotype blemishes could be rescued by injecting claudin h mRNA in vivo. Moreover, the immunohistochemistry experiment displayed the remarkable apoptosis of hair cells in the neuromast, which might contribute to the loss of hair cell number. Overall, these data indicated that claudin h is indispensable for the development of hair cells, vestibular function and hearing ability during zebrafish embryogenesis.